1998
DOI: 10.1002/(sici)1099-0488(19980415)36:5<851::aid-polb12>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and dynamic mechanical relaxation studies on poly(aryl ether ketone)s

Abstract: The relaxation behavior of four amorphous poly(aryl ether ketone)s was investigated using dielectric relaxation spectroscopy and dynamic mechanical analysis. The temperature dependence of the relaxation times of the glass transition process and the cooperative nature of this process were unaffected by changes in polymer structure. The temperature location of the loss peaks for all polymers progressed smoothly between the low frequency of the mechanical measurements and the higher frequencies of the dielectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 6 publications
3
18
1
2
Order By: Relevance
“…Accordingly, the interaction time increases for any given relaxation volume within the interaction volume under the sliding tip [11]. For the above calculated values for contact radii at a sliding speed of 500 nm=s, we find that the interaction time varies from 34 to 44 ms. With activation energies for of E a ¼ 11 eV and of E a ¼ 0:4-0:7 eV (typical for various PAEKs [13][14][15][16]), we obtain temperature shifts of 1 order of magnitude below the observed effect. Even if we consider the (aforementioned) length scale of cooperativity for the time scale estimation [22], we do not obtain the measured shift.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Accordingly, the interaction time increases for any given relaxation volume within the interaction volume under the sliding tip [11]. For the above calculated values for contact radii at a sliding speed of 500 nm=s, we find that the interaction time varies from 34 to 44 ms. With activation energies for of E a ¼ 11 eV and of E a ¼ 0:4-0:7 eV (typical for various PAEKs [13][14][15][16]), we obtain temperature shifts of 1 order of magnitude below the observed effect. Even if we consider the (aforementioned) length scale of cooperativity for the time scale estimation [22], we do not obtain the measured shift.…”
mentioning
confidence: 82%
“…The broad peak is caused by several individual relaxations. A transition at around 150 K has been previously observed for a closely related polymer, polyetheretherketone (PEEK) [13][14][15][16]. It has been shown that this relaxation is linked to a rotation of aromatic rings around the C-C bonds in the polymer backbone.…”
mentioning
confidence: 89%
“…The α relaxation is attributed to concerted rotational mobility of chain segments involving possibly 15 to 25 repeating units and appears as a sharp peak at 150°C. The second α relaxation is due to the relaxation of the newly formed crystal portion during the heating scan and appears as a shoulder at 165°C . The ionic conductivity was characterized by a large increase in the dielectric loss, ε ″, with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The testing procedure is carried out to verify if the renewable Pebax-b has properties comparable to those of the traditional Pebax-a currently adopted in the injection of the bellow. The testing procedures is based on a combination of tensile and bending mechanical tests, Dynamic Mechanical Analysis (DMA) (Ghosh et al 1998, Sheth et al 2003, Broadband Dielectric Spectroscopy (BDS) (Goodwin and Hay 1998, Kalakkunnath et al 2007, Viciosa et al 2007) and Thermogravimetric Analysis (TGA) (Boulares et al 2000, Wang et al 2007, Luyt et al 2010. All these tests are made both on not-degraded and degraded materials to estimate the possible response in the different conditions.…”
Section: Investigation Of Materials Propertiesmentioning
confidence: 99%
“…At lower frequencies the influence of the conductivity loss is emphasized. This contribution should be subtracted when analysing isothermal data for the investigation of -transition peak as well known from the Goodwin and Hay (1998) report.…”
Section: Experimental Testingmentioning
confidence: 99%